1991
DOI: 10.1128/aac.35.9.1741
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of drug-resistant influenza A virus during therapeutic use of rimantadine

Abstract: The therapeutic activity of rimantadine and its relationship to the shedding of drug-resistant influenza A virus were assessed in two randomized, double-blind, placebo-controlled trials involving patients with laboratory-documented influenza A virus (H3N2 subtype) illness of 2 days' duration or less. In a family-based study, rimantadine treatment for 10 days (24 children and adults) was associated with significant decreases in the number of days to a 50% reduction in symptoms (mean difference, 2.5 days), days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
3

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(90 citation statements)
references
References 15 publications
2
85
0
3
Order By: Relevance
“…However, only one of them was obtained from a patient who had received amantadine against influenza virus. Up to approximately one-third of the patients shed resistant viruses when amantadine or rimantadine is used for therapy (7,10,12). Transmission of drug-resistant viruses to close, sensitive contacts in families and other semi-closed settings has been described (5,6,9,12,14,(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
“…However, only one of them was obtained from a patient who had received amantadine against influenza virus. Up to approximately one-third of the patients shed resistant viruses when amantadine or rimantadine is used for therapy (7,10,12). Transmission of drug-resistant viruses to close, sensitive contacts in families and other semi-closed settings has been described (5,6,9,12,14,(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, drug-resistant virus can be isolated from humans as early as 2 days from the beginning of treatment with rimantadine (Hayden et al, 1991). Despite the rapid apThe next level of assay is in tissue culture, where the capacpearance of resistance, the drug displays a positive therapeutic ity of the inhibitors to stop multicycle replication of virus can benefit compared to placebo.…”
Section: (Yellow)mentioning
confidence: 99%
“…In an earlier study (Hall et al 1987), illness severity which scored late in therapy tended to be higher in rimantadine-treated children who shed resistant viruses compared to those who did not, but statistical signifi cance was not demonstrated. Furthermore, another study (Hayden et al 1991) indicated that average temperatures did not differ between the rimantadine groups over the fi rst 4 days of treatment, but a non-signifi cant elevation of temperature appeared that shed resistant virus on treatment day 5. Thus, the present study is the fi rst to show signifi cant recurrence and persistence of fever in children who shed resistant infl uenza viruses after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the clinical signifi cance of drug-resistant virus from treated patients, reduction of fever and improvement of daily scores for symptoms and severity of illness was used in the previous studies (Hall et al 1987;Thompson et al 1987;Hayden et al 1989Hayden et al , 1991. For this paper, only temperature data but not other symptoms was analyzed since it was the only objective measurement that was not affected by biases from doctors' or participants' feelings or judgments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation